Determinants of Sustainable Tourism Development Within the Socioeconomic Challenges - Md. Abdullah; Burhan Uddin; Md Abdullah Al Jamil (SocioEconomic Challenges)
Sustainable tourism is essential for ensuring the long-term viability of the tourism industry, particularly in areas facing significant socioeconomic challenges. By adopting sustainable practices, tourism can drive economic growth and job creation while safeguarding local communities from exploitation, displacement, or cultural erosion. This approach helps balance economic benefits with social and environmental responsibility, ensuring that tourism remains a positive force for both visitors and host communities. The objective of this research was to investigate the influence of environmental integrity, social equity, and economic prosperity on sustainable tourism development, focusing on archaeological heritage, while critically examining how socioeconomic challenges shape or hinder this process. Quantitative-type research was applied and the study used a descriptive research design. A standardized questionnaire was used to collect 150 data points from Bangladeshi expert tourists using a purposive sampling technique. The data were collected during the period of January to February 2025. A partial least square structural equation modeling (PLS-SEM) approach was used to evaluate the data and test the hypotheses. The results of the PLS-SEM analysis technique revealed that environmental integrity and economic prosperity had a positive relationship with sustainable tourism development in the setting of archeological heritage in Bangladesh. The research article offers practical recommendations for tourism authorities, such as the Bangladesh Tourism Board (BTB) and Bangladesh Parjatan Corporation (BPC), to enhance sustainable tourism development in archaeological heritage sites amid prevailing socioeconomic challenges. It highlights strategies to balance environmental integrity and economic prosperity, ensuring that tourism contributes positively to heritage preservation and local communities in Bangladesh.